2013
DOI: 10.1371/journal.ppat.1003133
|View full text |Cite
|
Sign up to set email alerts
|

Schmallenberg Virus Pathogenesis, Tropism and Interaction with the Innate Immune System of the Host

Abstract: Schmallenberg virus (SBV) is an emerging orthobunyavirus of ruminants associated with outbreaks of congenital malformations in aborted and stillborn animals. Since its discovery in November 2011, SBV has spread very rapidly to many European countries. Here, we developed molecular and serological tools, and an experimental in vivo model as a platform to study SBV pathogenesis, tropism and virus-host cell interactions. Using a synthetic biology approach, we developed a reverse genetics system for the rapid rescu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
136
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(148 citation statements)
references
References 54 publications
7
136
1
4
Order By: Relevance
“…Additional SBV pathogenesis studies in an experimental mouse model showed that SBV to replicate abundantly in neurons where it caused cerebral malacia and vacuolation of the cerebral cortex, thus reconfirming its strong neurotropism (Varela et al 2013). The SBV-induced acute lesions in experimental mice progressed from per-acute haemorrhages at 48 h post-infection to malacia at 72 h that extended to more widespread vacuolation of the white matter at 96-120 h post-inoculation.…”
Section: Pathogenesismentioning
confidence: 95%
See 4 more Smart Citations
“…Additional SBV pathogenesis studies in an experimental mouse model showed that SBV to replicate abundantly in neurons where it caused cerebral malacia and vacuolation of the cerebral cortex, thus reconfirming its strong neurotropism (Varela et al 2013). The SBV-induced acute lesions in experimental mice progressed from per-acute haemorrhages at 48 h post-infection to malacia at 72 h that extended to more widespread vacuolation of the white matter at 96-120 h post-inoculation.…”
Section: Pathogenesismentioning
confidence: 95%
“…The Gn and Gc proteins act as antigenic determinants and are recognised by neutralizing antibodies. The S RNA segment encodes the nucleocapsid protein (N) and non-structural protein (NSs) which plays a role in complement fixation (Elliott and Blakqori 2011;Goller et al 2012;Yanase et al 2012) and also in modulating the innate immune response of host cells Varela et al 2013). Of the three segments, the M RNA segment is the most variable among orthobunyaviruses.…”
Section: Aetiologymentioning
confidence: 99%
See 3 more Smart Citations